2015
DOI: 10.1038/jp.2015.1
|View full text |Cite
|
Sign up to set email alerts
|

Screening for cardiopulmonary events in neonates: a review of the infant car seat challenge

Abstract: The infant car seat challenge (ICSC), or period of observation in a car safety seat before discharge to monitor for episodes of apnea, bradycardia and desaturation, is one of the most common tests performed on preterm neonates in the United States. However, the utility of the ICSC to identify infants at risk for adverse cardiopulmonary events in the car seat remains unclear. Minimal evidence exists to guide clinicians in performance of this test including appropriate inclusion criteria and failure criteria. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…If the study had been conducted in a NICU not having guidelines requiring weekly blood tests when receiving HMF and/or phosphate, there might have been fewer visits in the NICU and more videoconferences. The American Academy of Pediatrics recommends observing for cardiorespiratory compromise in preterm infants while placed in a car seat prior to discharge for 90-120 minutes [28] however, this is not standard practice in NICUs in Denmark. During NTH there was one episode of desaturation/apnoea during transportation to the NICU, but this infant suffered from respiratory syncytial virus, which is a well-known risk-factor for apnoea in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…If the study had been conducted in a NICU not having guidelines requiring weekly blood tests when receiving HMF and/or phosphate, there might have been fewer visits in the NICU and more videoconferences. The American Academy of Pediatrics recommends observing for cardiorespiratory compromise in preterm infants while placed in a car seat prior to discharge for 90-120 minutes [28] however, this is not standard practice in NICUs in Denmark. During NTH there was one episode of desaturation/apnoea during transportation to the NICU, but this infant suffered from respiratory syncytial virus, which is a well-known risk-factor for apnoea in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that premature infants are prone to drops in blood oxygen saturation, and apnoea or hypoventilation when restrained in car seats, [2][3][4] in up to 60% of infants studied. 5 The American Academy of Pediatrics (AAP) recommends that all preterm infants should undergo monitoring in a car seat before discharge-for apnoea, bradycardia or desaturations, 6 7 and many UK hospitals follow this advice. The significance and potential impact of these problems is not clear, 8 9 but there have been reports of deaths of infants who have been left in a sitting position, including in car seats-both on journeys, and when parents have used it as an alternative to a pushchair or cot for the infant to sleep in.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although there is no consensus on failure criteria across the nation, our CSTS failure SpO 2 < 88% is conservative and lower than the most common cutoff of < 90%. 2,16 This may indicate that our findings are generalizable to those infants who have the more severe desaturation events. Further studies are needed to help define appropriate saturation limits for failure of CSTS.…”
Section: Discussionmentioning
confidence: 80%